Healthcare waste management in Germany - Hansen, Dorothea; Mikloweit, Ulrich; Ross, Birgit; Popp, Walter (International Journal of Infection Control, 2014)
Disposal of healthcare waste may pose complex problems because of the broad range of its composition. Household waste has to be managed as well as infectious and hazardous materials, parts of human origin from pathologies or operating theatres and recyclable waste. Occupational safety, legal and economic aspects have to be considered. German good practice guidelines to define, classify and treat medical waste are presented.